Therapeutic Effects of Modified Tempeh on Glycemic Control and Gut Microbiota Diversity in Diabetic Rats - Kusuma, Rio J.; Widada, Jaka; Huriyati, Emy; Julia, Madarina (Current Nutrition & Food Science, 2022)
Background: The role of the gut microbiota in improving glycemic control in diabetic patients is gaining attention. Tempeh is a fermented soy food from Indonesia that has antidiabetic and antidysbiotic effects. Interestingly, modification of tempeh processing by adding lactic acid bacteria has been reported to enhance the antidiabetic effect of tempeh. Aims: This study aimed to evaluate the effects of modified tempeh on serum glucose, insulin, and gut microbiota diversity of diabetic rats. Methods: Modified tempeh was developed by adding lactic acid bacteria from fermented cassava during tempeh processing. Diabetes was induced by injection of streptozotocin nicotinamide. Normal tempeh or modified tempeh was added to the diet and replaced 15% or 30% of casein. Serum glucose and insulin were analyzed before and after 30 days of intervention. At the end of the experiment, the appendix was sampled for gut microbiota analysis. Result: Modified tempeh has a significantly higher number of lactic acid bacteria (9.99 ± 0.09 versus 7.74 ± 0.07 log CFU, p < 0.001) compared to normal tempeh. There was a significant difference (p < 0.01) in serum glucose and insulin after treatment. Both tempeh supplements increased the diversity of the gut microbiota. Gut microbiota diversity has a strong negative correlation with delta glucose (r = -0.63, p < 0.001) and delta insulin resistance index (r = -0.54, p = 0.003). Conclusion: Modified tempeh has potential therapeutic antidiabetic activity, possibly through increased diversity of the gut microbiota.
Keywords: fermented cassava